FAKTOR PENARIK DAN PENDORONG WISATAWAN JEPANG BERKUNJUNG KE BALI - Indah Kusumarini (JURNAL KEPARIWISATAAN, 2011)
Japanese tourists are one of the most important markets of Balinese tourism, therefore understanding Japanese tourists is very crucial. This research, therefore, aims to identify Japanese tourists' motivations visiting Bali; their needs and wants/ likes of tourist attractions; and the factors which stumble their visit plans to Bali. Theory of motivation ''push and pull/actor" and "migration theory" are used in analyzing the problems. By using accidental sampling technique, questionnaires are spread out at the international departure o/Ngurah Rai airport to 100 respondents and some respondents are also interviewed. The result shows that "relaxing" is the main motivation/actor of Japanese tourists to visit Bali. The ''physical" is dominant as the travel motivation of Japanese tourists. Meanwhile the main/actor of Japanese tourists visiting Bali is the "natural scenery" and the stumbling/actor is "security". It seems that "nature" in Bali has a high attraction; therefore Japanese tourists intend to relax in Bali. However, this condition is not supported by external/actors, such as security. It should be considered to balance them. ··ree factors in order to increase the visit of Japanese tourists to Bali.